STUDIES ON THE POPULATIONS OF SAURIDA TUMBIL (BLOCK) FROM INDIAN WATERS - Rao, K Venkata Subba (Indian Journal of Fisheries, 2011)
A. comparison of morphometric and meristic characters of S. tumbil respectively by means of analysis of covariance and analysis of variance indicated that there may be three populations of iS. tumbil in Indian waters, coniined to (1) Visakhapatnam-Kakinada, (2) Bombay-Mangalore, and (3) Tuticorin